Heat-resistant anti-crack low-warpage PETG / PCTG base material plate and plate

Through the specific proportion and modification treatment of PETG/PCTG substrate board, the heat resistance, crack resistance, low warpage and high strength problems of PETG/PCTG in environmentally friendly floor substrates are solved, and the environmental protection performance and high performance requirements of ‘Non-PVC’ floors are achieved, and the application fields are expanded.

CN120365707APending Publication Date: 2025-07-25ZHEJIANG HAILIDE NEW MATERIAL +2

Patent Information

Application Number
CN202510505073.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-22
Publication Date
2025-07-25

AI Technical Summary

Technical Problem

The prior art lacks attempts to use PETG/PCTG to make ‘Non-PVC’ environmentally friendly floor substrates, especially in terms of heat resistance, crack resistance, low warpage, impact resistance, high strength and other properties.

Method used

PETG/PCTG base plates are prepared by modifying glass fibers and combined with injection molding process to ensure the heat resistance, crack resistance, low warpage and high strength of the material.

Benefits of technology

It realizes the environmental protection performance of PETG/PCTG substrate board, and has the characteristics of heat resistance, crack resistance, low warpage, impact resistance, high strength, etc., which expands its application in the field of floor substrates, and the process is simple and easy to industrialize.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005369549720000051
    Figure BDA0005369549720000051
  • Figure BDA0005369549720000061
    Figure BDA0005369549720000061
  • Figure BDA0005369549720000071
    Figure BDA0005369549720000071
Patent Text Reader

Abstract

The invention belongs to the technical field of plastic plates, and particularly relates to a heat-resistant anti-crack low-warpage PETG / PCTG base material plate and a plate. The PETG / PCTG base material plate is prepared from PETG resin, PCTG resin, modified glass fibers, a compatilizer, a chain extender, a lubricant and an antioxidant according to a specific ratio, wherein the modified glass fibers are sequentially modified by KH550 and oleic acid; the base material plate can be subjected to injection molding by adopting an injection molding process, has the characteristics of heat resistance, crack resistance, low warping, impact resistance, high strength and the like, and is suitable for preparing plates with special requirements, such as floors and the like. The board comprises a floor, a building wallboard and the like, a PETG / PCTG base material board is used as a main body, and a transparent film and a color film made of PETG materials can be further attached to the board.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of plastic sheets, and particularly relates to a heat-resistant, crack-resistant and low-warpage PETG / PCTG base plate and sheet. Background Art

[0002] With the proposal of environmental protection concepts such as "Non-PVC" and "PVC-Free" in recent years, non-PVC (polyvinyl chloride) materials such as PP (polypropylene) and PET (polyethylene terephthalate) have been continuously applied in the building materials field. PET is a crystalline polymer with poor processing performance and insufficient thermal stability, which cannot meet the daily use of floors. PETG (polyethylene terephthalate-1,4-cyclohexanedimethanol ester) and PCTG (polyethylene terephthalate-1,4-cyclohexanedimethanol ester) are amorphous materials with excellent processability, environmental protection, high toughness and chemical resistance. In addition, compared with PETG, PCTG also has better weather resistance, which can make up for the deficiencies of PETG in practical applications. However, the strength and rigidity of PETG and PCTG are relatively low. If glass fibers are filled, the glass fibers are polar minerals and are prone to agglomeration, and the interfacial adhesion with the resin is poor, resulting in poor mechanical properties of the composite material. Therefore, it is urgent to improve the surface properties of glass fibers so that they can be well adhered to the resin.

[0003] There is little research on the use of PETG for sheets such as floors. Most of them are used as color film or transparent film materials to facilitate the addition of colorants or as wear-resistant layers and elastic layers, such as CN219706385U (a corrosion-resistant and flame-retardant PETG floor film), CN212453480U (an environmentally friendly floor), etc. CN10451269C (a surface laminate resistant to casters) uses PETG and PCTG for floors, but only as a resin layer rather than a base layer, to improve the caster resistance, waterproofness, etc. by virtue of their toughness, elasticity, water resistance, etc. And materials such as PVC and PET have the same characteristics, so PVC, PE, etc. can be used for replacement. There are only a few studies on using PETG for the base layer. For example, CN112009060A (an environmentally friendly floor made of PETG and its manufacturing process) uses single-extruded PETG as the floor base layer and uses PETG for the wear-resistant layer and the decorative layer.

[0004] CN114230983A (a scratch-resistant transparent hard resin composite material, its preparation method and application) uses PCTG and SMMA in combination and finds that the combination of the two can improve the scratch resistance and hardness of PCTG, so it can be used for heat protection covers and touch screens.

[0005] So far, there has been a lack of attempts and reports in the industry to use PETG / PCTG to produce "Non-PVC" environmentally friendly floor substrates. There is also a lack of relevant performance research and reports on the application scenarios that require heat resistance, crack resistance, low warping, impact resistance, and high strength, such as the use of their mixture for floor substrates. Summary of the Invention

[0006] In view of the above problems, the present invention provides a heat-resistant, crack-resistant, and low-warping PETG / PCTG substrate board and sheet material, which while meeting the environmental protection performance of the substrate board, improve its heat resistance, crack resistance, low warping, impact resistance, high strength and other characteristics, making it suitable for preparing sheet materials with special requirements such as floor substrate boards. The technical solution of the present invention is as follows:

[0007] First of all, the present invention provides a PETG / PCTG substrate board with comprehensive advantages such as heat resistance, crack resistance, low warping, and impact resistance. The PETG / PCTG substrate board is made of raw materials with the following weight ratios: 50-70 parts by weight of PETG resin, 20-40 parts by weight of PCTG resin, 150-200 parts by weight of modified glass fiber, 2-8 parts by weight of compatibilizer, 1-3 parts by weight of chain extender, 1-6 parts by weight of lubricant, and 0.5-3 parts by weight of antioxidant; the modified glass fiber is sequentially modified with KH550 and oleic acid.

[0008] Preferably, the compatibilizer is selected from one or more of AS-g-MAH, SEBS-g-GMA, POE-g-GMA, ABS-g-MAH, POE-g-MAH. Further preferably, the compatibilizer is POE-g-MAH.

[0009] Preferably, the chain extender is selected from one or more of epoxy, oxazoline, isocyanate, anhydride. Further preferably, the chain extender is selected from one or more of styrene-glycidyl methacrylate, 2,2-(1,3-phenylene)-bis(2-oxazoline), triglycidyl isocyanurate, pyromellitic dianhydride. Still further preferably, the chain extender is triglycidyl isocyanurate.

[0010] Preferably, the lubricant is selected from one or more of zinc stearate, erucamide, ethylene bisstearamide, PE wax, EAA wax, mineral white oil. Further preferably, the lubricant is PE wax.

[0011] Preferably, the antioxidant is selected from one or more of hindered phenols, aromatic amines, phosphite esters, sulfur-containing esters. Further preferably, the antioxidant is selected from one or more of antioxidant 1010, antioxidant 5057, antioxidant 626, dilauryl thiodipropionate. Still further preferably, the antioxidant is antioxidant 1010.

[0012] Preferably, the method for preparing the aforementioned PETG / PCTG base plate comprises the following steps:

[0013] S1: Dehumidify and dry the PETG resin and PCTG resin at 60°C to 80°C for 6 to 8 hours, and set aside;

[0014] S2: Prepare a water-ethanol mixed solution according to a volume ratio of 1:(4 to 6). Add KH550 with a mass percentage of 4% to 6% to the water-ethanol mixed solution to obtain a KH550 water-ethanol solution. Add glass fiber to the KH550 water-ethanol solution and soak it at 70°C to 90°C for 7 to 9 hours. After soaking, take out the glass fiber and dry it. Then add the dried glass fiber to deionized water at 70°C to 90°C. Add oleic acid with a mass percentage of 5% to 7% of the mass of oleic acid and water to the deionized water and stir and react for 7 to 9 hours, and wash to obtain modified glass fiber;

[0015] S3: Place the PETG resin, PCTG resin, compatibilizer, chain extender, lubricant, and antioxidant in a high-speed mixer according to the parts by mass of the raw materials and mix for 10 to 30 minutes to obtain a mixed material;

[0016] S4: Add the mixed material from the barrel and add the modified glass fiber from the side feeder, and extrude and pelletize at 160°C to 220°C through a twin-screw extruder to obtain PETG / PCTG mixed particles;

[0017] S5: Inject and form the PETG / PCTG mixed particles into a plate at 230°C to 260°C. The injection molding process is an injection pressure of 110 to 130 PMa, an injection speed of 80 to 120 g / s, an injection time of 4 to 6 s, a holding pressure of 90 to 110 MPa, a holding time of 4 to 6 s, and the temperature of the mold temperature machine is 30 to 60°C.

[0018] Secondly, the present invention provides a floor made of the aforementioned PETG / PCTG base plate. A color film and a transparent film are pasted on the surface of the PETG / PCTG base plate, and the color film and the transparent film are made of PETG material.

[0019] Finally, the present invention provides a building wall panel made of the aforementioned PETG / PCTG base plate. A color film and a transparent film are pasted on the surface of the PETG / PCTG base plate, and the color film and the transparent film are made of PETG material.

[0020] Beneficial effects:

[0021] The PETG / PCTG base board of the present invention realizes environmental protection concepts such as "Non-PVC" and "PVC-Free". At the same time, the prepared PETG / PCTG base board has characteristics such as heat resistance, crack resistance, low warpage, impact resistance, and high strength, making it suitable for preparing boards with special requirements such as floor base boards. Thus, it also expands the application fields of PETG / PCTG materials and provides broad prospects for their market application in the field of floor base materials.

[0022] The PETG / PCTG base board of the present invention can be injection molded into a board by an injection molding process, and the preparation process is simple, which is conducive to industrial promotion and application. Specific embodiments

[0023] In order to better illustrate the purpose and technical solutions of the present invention, the present invention will be further described below in conjunction with specific experimental examples and comparative examples. It should be understood that the specific embodiments are only used to explain the present invention and are not used to limit the protection scope of the present invention.

[0024] The materials used in the examples are all conventional materials sold on the market. PETG is purchased from Henan Yindada New Materials Co., Ltd., model YH101; PCTG is purchased from SK Chemicals Korea, model YF300; POE-g-MAH (maleic anhydride grafted ethylene-octene copolymer elastomer) is purchased from Jia Yirong Polymer (Shanghai) Co., Ltd., model FB621; glass fiber is purchased from Taishan Fiberglass Co., Ltd.; TGIC (triglycidyl isocyanurate) is purchased from Huangshan Huahui Technology Co., Ltd., model HT-702; PE wax is purchased from Hebei Tianyu Chemical Co., Ltd.; antioxidant 1010 is purchased from Tianjin Lian Anlong New Materials Co., Ltd.

[0025] The following experimental examples and comparative examples prepare composite base boards by the following methods (materials not used in the comparative examples can be removed in the corresponding steps. For example, if unmodified glass fiber is not used, it is replaced with unmodified ordinary glass fiber; if PETG resin or PCTG or POE-g-MAH is not used, the material is removed in the corresponding drying or mixing steps). The specific steps are as follows:

[0026] S1: Dehumidify and dry the PETG resin and PCTG resin at 60°C to 80°C for 6 to 8 hours, and set aside.

[0027] S2: Prepare a water-ethanol mixed solution according to a volume ratio of 1:(4 - 6). Add KH550 with a mass percentage of 4% - 6% to the water-ethanol mixed solution to obtain a KH550 water-ethanol solution. Add glass fibers to the KH550 water-ethanol solution and soak them at a temperature of 70°C - 90°C for 7 - 9 h. After soaking, take out the glass fibers and dry them. Then add the dried glass fibers to deionized water at 70°C - 90°C, add oleic acid with a mass percentage of 5% - 7% of the mass of oleic acid and water, and stir and react for 7 - 9 h, and wash to obtain modified glass fibers.

[0028] S3: Place PETG resin, PCTG resin, compatibilizer, chain extender, lubricant, and antioxidant in a high-speed mixer according to the mass parts of raw materials and mix for 10 - 30 min to obtain a mixed material.

[0029] S4: Add the said mixed material into the barrel, and add modified glass fibers from the side feeder. Extrude and pelletize at 160°C - 220°C through a twin-screw extruder to obtain PETG / PCTG mixed pellets.

[0030] S5: Inject the PETG / PCTG mixed pellets into a plate at a temperature of 230°C - 260°C. The injection molding process is injection pressure 110 - 130 PMa, injection speed 80 - 120 g / s, injection time 4 - 6 s, holding pressure 90 - 110 MPa, holding pressure time 4 - 6 s, and the temperature of the mold temperature controller 30 - 60°C.

[0031] The compatibilizer can be selected from one or more of AS-g-MAH (acrylonitrile-styrene copolymer grafted maleic anhydride), SEBS-g-GMA (hydrogenated styrene-butadiene block copolymer grafted glycidyl methacrylate), POE-g-GMA (polyolefin elastomer grafted glycidyl methacrylate), ABS-g-MAH (acrylonitrile-styrene-butadiene copolymer grafted maleic anhydride), and POE-g-MAH. Further preferably POE-g-MAH.

[0032] The chain extender can be selected from one or more of epoxy-based, oxazoline-based, isocyanate-based, and anhydride-based. Further preferably styrene-glycidyl methacrylate (KL-E4370) in epoxy-based; 2,2-(1,3-phenylene)-bis(2-oxazoline) (PBO) in oxazoline-based; triglycidyl isocyanurate (TGIC) in isocyanate-based; pyromellitic dianhydride (PMDA) in anhydride-based.

[0033] The lubricant can be selected from one or more of zinc stearate, erucamide, EBS (ethylene bisstearamide), PE wax, EAA wax, and mineral white oil. Further preferably PE wax.

[0034] Among them, the antioxidant can be selected from one or more of hindered phenols, aromatic amines, phosphites, and sulfur-containing esters. Further preferably, it is antioxidant 1010 among hindered phenols, antioxidant 5057 among aromatic amines, antioxidant 626 among phosphites, and ditridecyl thiodipropionate (DTDTP) among sulfur-containing esters.

[0035] Preparation of Different Substrate Boards in Example 1

[0036] The following are the preparation methods of different experimental example substrate boards and comparative example substrate boards according to the aforementioned preparation method in the "Specific Embodiment". The ingredients (weight part ratios) of different experimental example substrate boards and comparative example substrate boards are shown in Table 1 and Table 2.

[0037] In the preparation of the experimental example substrate boards and comparative example substrate boards, the following process parameters are uniformly followed:

[0038] In step S1, the dehumidifying and drying temperature of the PETG resin and PCTG resin is 70 °C, and the time is 7 h.

[0039] In step S2, the volume ratio of water to ethanol in the water-ethanol mixed solution is 1:5; the mass percentage concentration of KH550 in the KH550 water-ethanol solution is 5%; the immersion temperature of the glass fiber in the KH550 water-ethanol solution is 80 °C, and the immersion time is 8 h; the dried glass fiber is added to deionized water at 80 °C, 5% oleic acid is added to the deionized water and stirred and reacted for 8 h, and the modified glass fiber is obtained by washing.

[0040] In step S3, the mixing time in the high-speed mixer is 15 min.

[0041] In step S4, granulation is carried out by extrusion through a twin-screw extruder at 220 °C.

[0042] In step S5, S5: The mixed particles are injection molded into a board at 240 °C, and the injection molding process is injection pressure 120 PMa, injection speed 100 g / s, injection time 5 s, holding pressure 100 MPa, holding pressure time 5 s, and the temperature of the mold temperature machine is 40 °C.

[0043] The thickness and other dimensions of each experimental example substrate board and comparative example substrate board are the same.

[0044] Table 1 Ingredient Table of Experimental Example Substrate Boards (Weight Parts)

[0045] Raw materials Experimental Example 1 Experimental Example 2 Experimental Example 3 Experimental Example 4 PETG 70 50 70 70 PCTG 20 40 20 20 POE-g-GMA 6 6 6 3 Modified glass fiber 200 200 150 200 TGIC 2 2 2 2 PE wax 3 3 3 3 Antioxidant 1010 1.5 1.5 1.5 1.5

[0046] Table 2 Ingredient Table of Comparative Example Substrate Boards (Weight Parts)

[0047]

[0048]

[0049] Performance Test of Different Substrate Boards in Example 2

[0050] Under the same test conditions, comprehensive performance tests were carried out on the experimental substrate boards prepared according to Example 1 and the substrate boards of the comparative example.

[0051] (1) Warpage Test: Test according to ISO24342 standard. The samples were cut into squares of 250mm×250mm×4mm, placed on a flat table, and each corner of the sample was tested one by one with a feeler gauge. The maximum value among the four corners was selected as the test result.

[0052] (2) Thermal Shrinkage Test: Test according to ISO24342 standard. The samples were cut into squares of 250mm×250mm×4mm, and the length and width of the samples were measured (both the four sides need to be measured and the data recorded. The length is recorded as L10 and L20, and the width is recorded as W10 and W20). The samples were placed in an 80°C oven, taken out after 6h, placed in the laboratory and left to stand for 3h. After standing, the length and width of the samples were tested (the length is recorded as L11 and L21, and the width is recorded as W11 and W21). Calculate: Length: {[(L10 + L20) / 2 - (L11 + L21) / 2] / [(L10 + L20) / 2]}×100%; Width: {[(W10 + W20) / 2 - (W11 + W21) / 2] / [(W10 + W20) / 2]}×100%. The maximum value was selected as the test result.

[0053] (3) Izod Impact Strength: Test according to GB / T1043.1 - 2008 standard. Cut into standard specimens of 80mm×10mm×4mm. Place the specimen to be tested at the place to be tested on the impact strength tester, set the weight of the pendulum and the impact energy, and then conduct the test.

[0054] (4) Elastic Modulus and Static Bending Strength Test: Test according to GB / T17657 - 2013 standard. Cut a sample of 150mm×50mm×4mm, measure the thickness of the sample, place the sample on the support rollers of the universal mechanical testing machine, and input the thickness of the sample before testing.

[0055] (5) Heat Deflection Temperature: Test according to ASTM D648 standard. 80mm×10mm×4mm. Install the sample on the heat deflection temperature test equipment to ensure good contact between the specimen and the equipment, and avoid problems such as poor heat conduction or specimen detachment. Set parameters such as the heating rate, test temperature range, and deformation amount, start the test equipment, start heating and observe the deformation of the specimen. When the specimen reaches the preset deformation amount, the equipment will automatically record the temperature value at this time.

[0056] (6) Wheelchair test: Test according to EN425 standard. Groove the sample to make a U-shaped buckle or a vertical buckle, cut it into a specific shape for splicing, fix the spliced sample on the wheelchair tester, and set different rotation speeds for testing.

[0057] (7) Falling ball impact: Test according to EN13329 standard. Take a 300mm×250mm×4mm sample and place it on the chassis of the falling ball impact testing machine, and fix it with screws. Drop an iron ball from a high place for impact testing.

[0058] Table 3 Test results of the substrate board performance in experimental examples

[0059]

[0060] Table 4 Test results of the substrate board performance in comparative examples

[0061]

[0062] It can be seen from Tables 3 and 4 that for the PETG / PCTG composite substrate board of the present invention (Experimental Examples 1 to 4), the warpage ≤ 0.85 mm, the thermal shrinkage rate ≤ 0.10%, the notched Izod impact strength ≥ 8.6 kJ / m 2 , the elastic modulus ≥ 3220 MPa, the flexural strength ≥ 22 MPa, the heat distortion temperature ≥ 82 °C, the wheelchair test ≥ 25500 r, and there is no cracking in the falling ball impact. The comprehensive performance indicators are all superior to those of the substrate boards in Comparative Examples 1 to 4.

[0063] Although Comparative Examples 2 and 3 also use PETG / PCTG composite materials, there are still problems such as easy warpage, low heat distortion temperature, easy cracking, etc., and the wheelchair test effect is not ideal, resulting in being unsuitable as a floor substrate. It can be seen that when PETG / PCTG is used as a floor substrate, its dosage and the like have a significant impact on the performance. The substrate board of Comparative Example 1 has good characteristics such as low warpage, low shrinkage, and impact resistance, which conforms to the characteristics of PETG, but its heat distortion temperature is relatively low and it is easy to crack.

[0064] Based on the above results, it can be known that the PETG / PCTG composite substrate board provided by the present invention is mainly prepared by mixing modified glass fiber, PETG resin, PCTG resin, etc., extruding and granulating first, and then injection molding. Among them, the substrate board provided by the present invention uses a blend of PETG and PCTG resins to replace the traditional polyvinyl chloride resin, and further introduces modified glass fiber as the skeleton. While ensuring toughness and thermal stability, it effectively improves the rigidity of the PETG / PCTG substrate board. Compared with the existing plastic floors, the plastic floor prepared from the substrate board of the present invention has comprehensive advantages such as environmental protection, low warpage, rigid-flexible balance, and thermal stability.

[0065] Example 3 Floor / Wallboard Based on PETG / PCTG Substrate Board and Preparation

[0066] The PETG / PCTG substrate boards prepared in Experimental Examples 1 to 4 can be further laminated with a color film and a transparent film to make a floor / wall panel with a color film and a transparent film.

[0067] Among them, for the laminated color film and transparent film, PETG color film and PETG transparent film can be selected respectively. The thicknesses of the color film and the transparent film can be set according to actual requirements. For example, the thickness of the color film is 1 mm, and the thickness of the transparent film is 2 - 3 mm.

[0068] Among them, the color film and the transparent film can adopt the hydraulic lamination process, and the specific process parameters are as follows:

[0069] Hot machine temperature 150 °C, hot machine pressure 3 MPa, hot pressing time 20 min, cold machine temperature 20 °C, cold machine pressure 7 MPa, cold pressing time 4 min.

[0070] It should be noted that although the technical solutions of the present invention have been described in detail in the above embodiments, these embodiments are only illustrative examples rather than restrictive definitions. Those skilled in the art should understand that any modification or equivalent replacement made without departing from the spirit and scope of the technical solution of the present invention should be included within the scope of the claims of the present invention. Therefore, the protection scope of the present invention should be determined by the content defined in the claims.

Claims

1. A heat-resistant, crack-resistant and low-warpage PETG / PCTG base plate, characterized in that the PETG / PCTG base plate is made of raw materials in the following weight ratio: 50-70 parts by weight of PETG resin, 20-40 parts by weight of PCTG resin, 150-200 parts by weight of modified glass fiber, 2-8 parts by weight of compatibilizer, 1-3 parts by weight of chain extender, 1-6 parts by weight of lubricant, and 0.5-3 parts by weight of antioxidant; the modified glass fiber is successively modified with KH550 and oleic acid.

2. The heat-resistant, crack-resistant and low-warpage PETG / PCTG base plate according to claim 1, wherein, The compatibilizer is selected from one or more of AS-g-MAH, SEBS-g-GMA, POE-g-GMA, ABS-g-MAH, and POE-g-MAH.

3. The heat-resistant, crack-resistant and low-warpage PETG / PCTG base plate according to claim 1, characterized in that, The chain extender is selected from one or more of epoxy, oxazoline, isocyanate, and anhydride.

4. A heat-resistant, crack-resistant and low-warpage PETG / PCTG base plate according to claim 3, characterized in that, The chain extender is selected from one or more of styrene-glycidyl methacrylate, 2,2-(1,3-phenylene)-bis(2-oxazoline), triglycidyl isocyanurate, and pyromellitic dianhydride.

5. A heat-resistant, crack-resistant and low-warpage PETG / PCTG base plate according to claim 1, wherein The lubricant is selected from one or more of zinc stearate, erucamide, ethylene bisstearamide, PE wax, EAA wax, and mineral white oil.

6. The heat-resistant, crack-resistant and low-warpage PETG / PCTG base plate according to claim 1, wherein The antioxidant is selected from one or more of hindered phenols, aromatic amines, phosphite esters, and sulfur-containing esters.

7. A heat-resistant, crack-resistant and low-warpage PETG / PCTG substrate board according to claim 6, characterized in that The antioxidant is selected from one or more of antioxidant 1010, antioxidant 5057, antioxidant 626, and dilauryl thiodipropionate.

8. A heat-resistant, crack-resistant and low-warpage PETG / PCTG base plate according to any one of claims 1 to 7, characterized in that, The preparation method of the PETG / PCTG base plate comprises the following steps: S1: Dehumidify and dry the PETG resin and PCTG resin at 60°C - 80°C for 6 - 8 h, and set aside; S2: Prepare a water-ethanol mixed solution according to a volume ratio of 1:(4 - 6). Add KH550 with a mass percentage of 4% - 6% to the water-ethanol mixed solution to obtain a KH550 water-ethanol solution. Add glass fiber to the KH550 water-ethanol solution, soak it at 70°C - 90°C for 7 - 9 h, take out the glass fiber after soaking and dry it; then add the dried glass fiber to deionized water at 70°C - 90°C, add oleic acid and oleic acid with a mass percentage of 5% - 7% of water to the deionized water and stir and react for 7 - 9 h, and wash to obtain modified glass fiber; S3: Place the PETG resin, PCTG resin, compatibilizer, chain extender, lubricant, and antioxidant in a high-speed mixer according to the mass parts of the raw materials and mix for 10 - 30 min to obtain a mixed material; S4: Add the mixed material from the barrel and add the modified glass fiber from the side feeder, and extrude and pelletize at 160°C - 220°C through a twin-screw extruder to obtain PETG / PCTG mixed particles; S5: Inject and form the PETG / PCTG mixed particles at a temperature of 230°C - 260°C. The injection molding process is injection pressure 110 - 130 PMa, injection speed 80 - 120 g / s, injection time 4 - 6 s, holding pressure 90 - 110 MPa, holding pressure time 4 - 6 s, and the temperature of the mold temperature machine 30 - 60°C.

9. A floor, comprising a base board, a color film and a transparent film adhered to the surface of the base board; characterized in that, The base substrate is the PETG / PCTG base substrate according to any one of claims 1 to 8; the color film and the transparent film are made of PETG material.

10. A building wall panel, comprising a base board and a color film and a transparent film adhered to the surface of the base board; characterized in that, The base substrate is the PETG / PCTG base substrate according to any one of claims 1 to 8; the color film and the transparent film are made of PETG material.

Citation Information

Patent Citations

  • Environment-friendly floor made of PETG material, and manufacturing process thereof

    CN112009060A

  • Environment-friendly floor

    CN212453480U

  • Corrosion-resistant and flame-retardant PETG floor film

    CN219706385U

Cited By

  • Optical-grade heat-resistant modified PETG material and preparation method thereof

    CN121949766A